Anti-hypertensive property of a nickel-piperazine/NO donor in spontaneously hypertensive rats. (May 2016) - Monti, Martina; Ciccone, Valerio; Pacini, Aurora; Roggeri, Riccardo; Monzani, Enrico; Casella, Luigi; Morbidelli, Lucia
Graphical abstract: Abstract: The nickel-piperazine/NO donor compound, Ni(PipNONO)Cl, belonging to the family of compounds labelled as "metal-nonoates", due to its promising vasodilating activity, has been considered as a potential drug candidate in anti-hypertensive therapy. Drug efficacy has been evaluated in spontaneously hypertensive rats (SHR) in comparison with normotensive animals (C57BL/6 mice and WKY rats). In normotensive animals the metal-nonoate maintained blood pressure at basal level both following acute administration and after 30 days of treatment. In SHR, Ni(PipNONO)Cl reduced blood pressure in the dose range of 3–10 mg/kg. When compared with a commercial NONOate, DETA/NO, used at the same doses, Ni(PipNONO)Cl was more active in reducing blood pressure in SHR than DETA/NO in the first two weeks, while the effect of the two molecules was similar in the third and fourth week. The degradation and control compound Ni(Pip)Cl2 had no effect on blood pressure and heart rate in same animal models. Remarkably, the blood pressure reduction induced by the new NO-donor Ni(PipNONO)Cl does not evoke changes in the heart rate and tolerance. Considering the mechanisms of vascular protection, 30 days of administration of Ni(PipNONO)Cl improved endothelial function in SHR by upregulating endothelial NO synthase (eNOS) through increased eNOS protein levels and downregulated Caveolin-1 (Cav-1), and by increasing superoxide dismutase 1 (SOD1) protein level in aortae. In cultured endothelial cells Ni(PipNONO)Cl restored the cell functions (cytoskeletal protein expression, migration and proliferation) altered by the inflammatory mediator interleukin-1β (IL-1β), impairing the endothelial to mesenchimal transition. In conclusion, Ni(PipNONO)Cl maintained unaltered blood pressure in normotensive mice and rats, and it exerted anti-hypertensive effect in SHR through the restoration of vascular endothelial protective functions.